Experiences in educommunication and formation in environmental education at Sala Verde “Observatory of education, health, citizenship and socio-environmental justice of Itajaí Valley (SC - Brazil)” (Citizenship in Action: Extension and Culture Magazine, 2024)
The article presents the experiences and actions of the Sala Verde Project “Education, Health, Citizenship and Socio-environmental Justice Observatory - Vale do Itajaí (SC)”, called Sala Verde Itajaí Project, in 2017. The “Salas Verdes” are a public policy of the Ministry of the Environment (MMA) of the Federal Government. In Itajaí (SC) the Sala Verde is managed by the University of Vale do Itajaí (UNIVALI) through the Environmental Education Laboratory (LEA) of the current Polytechnic School. From the critical and transforming perspective of Environmental Education, the results of the three subprojects are described and analyzed: “Educommunication and Circuito Tela Verde”; “Formation in Environmental Education for Participatory Management and Public Policies” and “Sala Verde Exhibition Space”, which are part of the political pedagogical project of Sala Verde Itajaí. The methodological processes adopted are detailed, which follow a continuous cycle of systematization involving the steps of "Planning - Executing - Evaluating - Communicating", in particular the production of educommunication of projects and extension actions of the LEA via digitization of its collection and updating of the its Educommunication Channel. Activities are based on ethical principles and the fight against oppression experienced by citizens, through integrated extension, teaching and research interventions. In addition, audiovisual and educommunication teaching materials are produced based on these actions, in collaboration with the social editors involved. Among these experiences, the following stand out: 1) Short film “More than Mud: Memories, Absences and History” co-edited with families affected by the socio-environmental crime of the mining companies Samarco, Vale and BHP Billiton in the municipality of Mariana (MG); 2) Video tutorial “How to make a homemade compost bin”; and 3) Interactive exhibition “It's Necessary to Have Strength!”. These experiences contemplated the use of audiovisual and aesthetic resources to encourage reflections and dialogues of knowledge about the socio-environmental problems of our society.
Keywords: art-education-environmental; heritage education; dialogues; Sala Verde Itajaí; public policies